Relasi Etnisitas dan Industrialisasi Era Kolonial Inggris di Malaysia - Muhaimin Zulkhair (Departemen Ilmu Hubungan Internasional Univesitas Hasanuddin, 2015)
Ethnicity and industrialization are usually analyzed separately. Even if seen interlink, the analysis usually focused on the industrial chains itself (actor proximity, component makers and industry sustainability). This paper intends to come out of that tradition and to be linked with the historical colonial practice that will give to a more comprehensive understanding. By taking the Malaysia colonial context is expected to show the linkages. The issue of ethnicity in this paper is not seen as something that stands alone and domestic but is related to the practice of the colonial political economy strategies to manage the problems become the dominant discourse.